Strategies and technical challenges for imaging oligometastatic disease: Recommendations from the European Organisation for Research and Treatment of Cancer imaging group. (March 2018) - deSouza, Nandita M.; Liu, Yan; Chiti, Arturo; Oprea-Lager, Daniela; Gebhart, Géraldine; Van Beers, Bernard E.; Herrmann, Ken; Lecouvet, Frederic E.
Abstract: Patients with oligometastatic disease (OMD) often have controllable symptoms, and cures are possible. Technical improvements in surgery and radiotherapy have introduced the option of metastasis-directed ablative therapies as an adjunct or alternative to standard-of-care systemic therapies. Several clinical trials and registries are investigating the benefit of these therapeutic approaches across several cancer sites. This requires that patients are correctly included and followed with appropriate imaging. This article discusses the evidence and offers recommendations for the implementation of standard-of-care (Response Evaluation Criteria in Solid Tumours measurements on computed tomography [CT], magnetic resonance imaging [MRI] and bone scintigraphy) and advanced imaging modalities (functional, metabolic and radionuclide targeted) for identifying and following up patients with OMD. Imaging requirements for recognising OMD vary with tumour type, metastatic location, and timing of measurement in relation to previous treatment. At each point in the disease cycle (diagnosis, response assessment and follow-up), imaging must be tailored to the clinical question and the context of prior treatment. The differential use of whole-body approaches such as 18 F-FDG-positron emission tomography (PET)/CT, diffusion-weighted MRI, 18 F-Choline-PET/CT and 68 Ga-prostate specific membrane antigen–PET/CT require rationalisation depending on clinical risk assessment. Optimal standardised imaging approaches will enable OMD trials to document patterns of disease progression and outcomes of treatment. Quality assured and quality controlled imaging data included in databases such as the European Organisation for Research and Treatment of Cancer Imaging platform for the Oligocare trial (a prospective, large-scale observational basket study being set up to collect outcome data from patients with OMD treated with radiation therapy) will establish a large and high-quality imaging warehouse for future research. Highlights: The imaging requirements for identifying patients with oligometastases are discussed. Recommendations are made for imaging oligometastases in four cancer types. Relevance of specific imaging at various points in the disease cycle is highlighted.